Acceptability of aggression among children who reside with substance-abusing parents: The influence of behavioral dysregulation, exposure to neighborhood violence, and interparental violence. Issue 4 (1st October 2016) - Kelley, Michelle L.; Braitman, Abby L.; Milletich, Robert J.; Hollis, Brittany F.; Parsons, Rachel E.; White, Tyler D.; Patterson, Cassie A.; Haislip, Brianna N.; Henson, James M.
ABSTRACT: The present study examined how interparental violence, neighborhood violence, behavioral regulation during parental conflict, and age predicted beliefs about the acceptability of aggression and the acceptance of retaliation against an aggressive peer among youths. Participants were 110 families (mothers, fathers, and children) in which one or both parents met criteria for substance use disorder. Results of a bootstrapped multivariate regression model revealed higher exposure to neighborhood violence predicted greater acceptability of general aggression, whereas higher father-to-mother violence perpetration predicted lower acceptability of general aggression. Higher exposure to neighborhood violence, behavioral dysregulation during parental conflict, and older child age predicted greater approval of retaliation toward an aggressive peer. Findings are interpreted as related to the cognitive-contextual framework.